Physiological Changes in the Levels of Anti-Cytokine Autoantibodies in Early Pregnancy Are Missing in Pregnant Women with Hashimoto’s Thyroiditis - Szabina Erdő-Bonyár; Diána Simon; Anna Bajnok; Jasper Nörenberg; Tímea Serény-Litvai; Ákos Várnagy; Kálmán Kovács; Eszter Hantosi; Emese Mezősi; Tímea Berki (Journal of Immunology Research)
T helper type 1 (Th1) and inflammatory cytokines play essential roles in early pregnancy and also in the pathogenesis of Hashimoto’s thyroiditis (HT). Changes in the serum level of autoantibodies to cytokines, which may be able to modulate their availability and actions have been described in several autoimmune disorders. Yet, no data are available on anti-cytokine autoantibodies either during early pregnancy or in patients with HT. The aim of the study was to measure autoantibodies to inflammatory-, Th1- and Th22-cytokines in serum samples in healthy pregnancy (HP) and in pregnant women with HT (HTP). As pathological autoantibodies are hallmarks of HT, in addition we also measured anti-B-cell activator factor (BAFF) autoantibodies. The measurement was carried out with a Luminex multiplex assay and the Luminex MAGPIX Instrument, age-matched healthy women (HC) and women with HT (HT) were used as controls. In the first trimester of HP, anti-TNFα, anti-IL-8, and anti-IFNγ autoantibodies were significantly decreased, while autoantibodies to BAFF were significantly elevated compared to the HC. However, these alterations were not present in the HTP. Moreover, the levels of autoantibodies to IL-22 and TNFα were significantly increased in HTP compared to the HP. All differences in the levels of the investigated autoantibodies could be detected in the first trimester of pregnancies except for anti-IL-22 autoantibodies. According to our results we can conclude that alterations in the levels of autoantibodies to inflammatory and Th1 cytokines are physiological in the first trimester of pregnancy and their disturbance can be associated with autoimmune conditions such as HT.